Recognition of Peculiarities of Territories at the Regional Policy in the Sphere of Social and Economic Development, Culture and Tourism - S. T. Rumiantceva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The implementation of a new regional policy that ensures integrated development of territories, employment of the population, creation of the necessary revenue base of budgets, is the most important problem of public administration. The purpose of this study is to determine the mechanisms for taking into account the territorial specifics in the formation and implementation of regional policies. The article reveals the criteria for identifying the types of regions depending on the conditions and factors of socio-economic development, the formation of regional functions in the sphere of culture and tourism. The necessary conditions for the effective use of the tourist and recreational potential are described, and the criteria for typologizing the territories for the purposes of conducting regional policy by the state administration are proposed.